Modernity, nation and urban-architectural form: the dynamics and dialectics of national identity vs regionalism in a tropical city - Jahn Kassim, Puteri Shireen (Palgrave Macmillan, 2018)
This book explores how Malaysia, as a multicultural modern nation, has approached issues of nationalism and regionalism in terms of physical expression of the built environment. Ever since the nation’s post-Colonial era, architects and policy makers have grappled with the theoretical and practical outcomes of creating public architecture that effectively responds to traditions, nationhood and modernity.